A method for quantification of human transporter proteins by liquid chromatography–tandem mass spectrometry. Issue 3 (17th February 2023) - Hou, Zhe; Zhang, Lei; Guo, Xuan; Li, Hui; Li, Xiaodong; Dong, Jing; Zhang, Guangqin; Liu, Dongyang
Abstract: The aim of this study was to develop a validated liquid chromatography–tandem mass spectrometry method to quantify nine important transporter proteins, so as to support the quantification of transporter proteins abundance in different human tissues and organs. Quantification was performed by targeted proteomics in positive multiple reaction monitoring mode with liquid chromatography–tandem mass spectrometry. The method was validated with respect to specificity, linearity, accuracy, precision, and stability. All the correlation coefficients (r) were larger than 0.99 and the validation ranges of multidrug‐resistant transporter 1, breast cancer resistance protein, organic cation transporter 2, and organic anion transporter 1 were 0.036–3.636 nM, organic anion transporter 3 was 0.018–1.818 nM, organic anion transporting polypeptide transporter 1B1 and multidrug and toxin extrusion transporter 1 were 0.091–9.091 nM, organic anion transporting polypeptide transporter 1B3 and multidrug and toxin extrusion transporter 2K were 0.182–18.182 nM. The results of intra‐day and inter‐day accuracy and precision were all in line with the quantification requirements of biological samples and the stability results indicated that the samples were stable under current processing and storage conditions. The method is sensitive and efficient for the quantification of nine transporters in human tissues.